PERANCANGAN SIKLUS AKUNTANSI PADA BANK SAMPAH - Afrida Yani; Lyandra Aisyah Margie; Habibah Habibah; Ahmad Syukri (S1 Accounting Program, Universitas Pamulang, 2019)
This community service has a general objective to help partners develop a good waste management system, good and correct accounting reporting, and build a model of the Waste Bank system, which can inform the quantity of waste in each village and the quantity of recycled waste to meet the economic needs of the community. The theme of PKM is financial accounting, by involving lecturers and resource persons Lecturers in the Accounting Study Program from Pamulang University. The results of the PKM Implementation carried out on 20, 21 and 22 October 2019 were to increase knowledge in the field of accounting, especially regarding the financial records of the participants of the Asri Berseri Garbage Bank Management group in Benda Baru, South Tangerang, Banten. The response of the participants was very good and happy because it was very helpful in learning about financial records. Suggestions submitted were PKM activities in the future to be carried out continuously so that the participants would always get guidance in recording the accounting cycle and provide financial reporting to the public related to the Garbage Bank, so that the community was more enthusiastic in collecting waste because it could provide high economic value. Keywords: Accounting cycle; Accounting records